Visual Presentation of Court Culture: The Seduction and Disenchantment in TV Series “The Crown” - Huang Ziqiang (SHS Web of Conferences, 2023)
Historical TV dramas have changed the narrative mode of historical events and their backgrounds and visually reproduced history for the audience with exquisite scene construction and costume. Different from traditional historical themes, the royal family and the court culture behind it rely on their unique distance from the public’s vision as the basis for their existence. The mystery of power is still very important to the monarchy in modern society. However, the visual entertainment of popular culture is trying to disintegrate it. This article takes the TV series “The Crown” about the British royal family launched by the streaming media company Netflix in 2016 as an example, uses case analysis as a research method, studies some of the key contents of the five-season TV series currently launched, and discusses the seduction and disenchantment of court culture behind the image in the TV series. The research results show that in the process of visual presentation of the royal family, the role of the media will simultaneously show the seduction to the audience and the audience’s breaking of this seduction, and this contradictory relationship also affects the palace itself behind the historical drama.